Intercropping Walnut and Tea: Effects on Soil Nutrients, Enzyme Activity, and Microbial Communities - Bai, Yong-Chao; Li, Bao-Xin; Xu, Chun-Yong; Raza, Mubashar; Wang, Qi; Wang, Qi-Zhu; Fu, Ya-Nan; Hu, Jian-Yang; Imoulan, Abdessamad; Hussain, Muzammil; Xu, Yong-Jie (Frontiers in Microbiology, 2022)
The practice of intercropping, which involves growing more than one crop simultaneously during the same growing season, is becoming more important for increasing soil quality, land use efficiency, and subsequently crop productivity. The present study examined changes in soil physicochemical properties, enzymatic activity, and microbial community composition when walnut (Juglans spp.) was intercropped with tea (Camellia sinensis L.) plants in a forest and compared with a walnut and tea monocropping system. The results showed that walnut-tea intercropping improved the soil nutrient profile and enzymatic activity. The soil available nitrogen (AN), available phosphorus (AP), available potassium (AK), organic matter content (OM), and sucrase activity were significantly boosted in intercropped walnut and tea than in monocropping forests. The interaction between crops further increased bacterial and fungal diversity when compared to monoculture tea forest. Proteobacteria, Bacteroidetes, Firmicutes, Gemmatimonadetes, Chlamydiae, Rozellomycota and Zoopagomycota were found in greater abundance in an intercropping pattern than in monoculture walnut and tea forest plantations. The walnut-tea intercropping system also markedly impacted the abundance of several bacterial and fungal OTUs, which were previously shown to support nutrient cycling, prevent diseases, and ameliorate abiotic stress. The results of this study suggest that intercropping walnut with tea increased host fitness and growth by positively influencing soil microbial populations.